Development of UV Spectroscopic Method for Nefopam and Escitalopram as INN Drugs in Tablet Dosage Form - Fatema, Kanij; Rahman, Md Zakiur; Biswas, Subrata Kumar; Akter, Suraia (Stamford Journal of Pharmaceutical Sciences, 2011)
Nefopam and Escitalopram are INN drugs and as such it has not been yet included in the BP or USP. The objective of this work is to develop a simple, sensitive, accurate, precise and reproducible UVSpectrophotometric method for quantitative estimation of Nefopam and Escitalopram in tablet dosage forms. Various solvents were used to find out the medium for maximum solubility of each drug. The χmax of Nefopam and Escitalopram was 266nm and 284nm in water respectively. Both drugs obey Beer- Lambert’s law in the range of 50-400μg/ml for Nefopam and 25-200μg/ml for Escitalopram. The correlation coefficients of std. curves were 0.998 and 0.995. The values of SD were 0.131 and 0.081 respectively. %RSD (Relative standard deviation) of interday absorbance of Nefopam was 0.766 and Escitalopram was 0.854. The LOD (Limit of Detection) were 0.393 and 0.243 and LOQ (Limit of Quantification) were 1.310 and 0.810 respectively. The percent potencies were 92.16 and 102.06 for Nefopam and Escitalopram. The potency of these tablets complied with their claimed quantity (±10%). So, based on these data, it may be concluded that these proposed method are simple, sensitive, precise, reproducible and accurate for the analysis of these drugs in tablet dosage form. Key Words: INN drugs; correlation coefficients; LOD; LOQ; Nefopam; Escitalopram. DOI: 10.3329/sjps.v3i1.6791 S. J. Pharm. Sci. 3(1): 4-10